KAJIAN BANGKITAN LALU LINTAS DAMPAK PEMBANGUNAN CIREBON SUPER BLOCK - Akbardin, Juang; Arie Wibowo, Didi (ASTONJADRO, 2013)
To predict the trip generation at Cirebon Super Block, needed domestic social data on the zone where the Cirebon Super Block is located, in this case the social data is sampled households in the Pekiringan Kesambi Cirebon. Data obtained from the Transportation Department of Cirebon City as household data in 2004 which contains a number of trips, household size, vehicles owned, and monthly income. Data obtaines from these generation trip model of Y = 4.76 + 0.45 X1 - 0.53 X2 + 0.50 X3 with koefien test results of determination 0.917.